2019
DOI: 10.1108/qmr-02-2017-0058
|View full text |Cite
|
Sign up to set email alerts
|

Exploring social media addiction among student Millennials

Abstract: Purpose -The purpose of this paper is to explore the phenomenon of social media addiction among student Millennials. The authors use the consumption continuum as a theoretical framework.Design/methodology/approach -The authors used a "media deprivation" methodology including both qualitative and quantitative measures.Findings -The authors found that social media may exist in some respondents in a "near addiction" phase or the "social media addiction" phase according to the consumption continuum framework. Seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 40 publications
0
43
0
1
Order By: Relevance
“…SMTs have not been shown to cause physical addiction (akin to the physiological craving for nicotine), but there is growing evidence that they can be responsible for psychological addiction (in a comparable sense to how persons can be addicted to gambling). Currently, the evidence concerning the addictive nature of SMTs is mixed (Grau et al, 2019 ; D’Arienzo et al, 2019 ), but some users clearly find them addictive. This indicates that we have reason to think of them more like cigarettes, rather than fast-food.…”
Section: Problems With the Mcdonald’s Modelmentioning
confidence: 99%
“…SMTs have not been shown to cause physical addiction (akin to the physiological craving for nicotine), but there is growing evidence that they can be responsible for psychological addiction (in a comparable sense to how persons can be addicted to gambling). Currently, the evidence concerning the addictive nature of SMTs is mixed (Grau et al, 2019 ; D’Arienzo et al, 2019 ), but some users clearly find them addictive. This indicates that we have reason to think of them more like cigarettes, rather than fast-food.…”
Section: Problems With the Mcdonald’s Modelmentioning
confidence: 99%
“…While there are a number of studies conducted into social media addiction (Olowu and Seri, 2012;Al-Menayes, 2015;Nakaya, 2015;Yu et al,2015;Bányai et al,2017;Balakrishnan and Griffiths, 2017;Griffiths and Kuss, 2017 ;Hawi and Samaha, 2017;Monacis et al, 2017;Azizi, Soroush and Khatony, 2019;Casale, Rugai and Fioravanti, 2018;Grau, Kleiser and Bright, 2019;Hou et al, 2019;Sun and Zhang, 2020), this study focuses on other studies that have been conducted in Turkey and that deal with social media addictions of teacher candidates. Studies undertaken in Turkey concentrate on Generation Z.…”
Section: Social Media Addictionmentioning
confidence: 99%
“…While Facebook has 1.95 billion active users from these social media platforms, Instagram has 925.5 million, Linkedin 663.3 million, Snapchat 381.5 million and Twitter 339.6 million active users (Kemp, 2020). Social media addiction is sometimes an expression used to refer to someone who spends a lot of time using Facebook, Twitter, Instagram or other social media platforms, and this time affects other aspects of daily life (Grau, Kleiser, & Bright, 2019).…”
Section: Social Media Addictionmentioning
confidence: 99%
“…Research has shown that various online activities, such as constant online gaming and social media use, can be addictive to a particular group, especially adolescents and adults (Cheng & Li, 2014;Kuss, Griffiths, Karila, & Billieux, 2014;Ryan, Chester, Reece, & Xenos, 2014). Social media sites are particularly important for Millennium college students, who have been determined to spend a lot of time online and use the Internet frequently for social purposes (Grau et al, 2019). Especially in developed and developing countries, the development of the Wi-Fi network and the fact that 60% to 95% of the young adults all have smart phones, and the rapid increase in the number of applications developed for smart phones are the factors that cause the growth of social media usage of people (Yang, Chen, Huang, Lin, & Chang, 2017).…”
Section: Social Media Addictionmentioning
confidence: 99%